2013
DOI: 10.4172/2161-0932.1000185
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of High Risk Oncogenic Human Papillomavirus Types in Cervical Smears of Women Attending Well Woman Clinic in Ile Ife, Nigeria

Abstract: This study is aimed at estimating the prevalence of cervical infection with High risk Human Papillomavirus (HR-HPV) in cervical smears of women attending the Well Woman Clinic of the Obafemi Awolowo University Teaching Hospital Complex, Ile-Ife. This is a community based clinic where women are screened for cervical, breast and other female related diseases. This is a prospective cross-sectional observational study. Information was obtained through personal interviews using structured questionnaire. Cervical sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…6 A study done in Ile Ife, Nigeria by Fadahunsi et al in 2013 showed that the commonest high-risk HPV type infection in women are 16, 53, 18 and 52. 33 Macroscopically, the tumour can be exophytic or endophytic invading surrounding structures. 10,14 The keratinizing type is composed of whorls of malignant squamous epithelial cells with individual keratinization that may be surrounding pearls of keratin.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…6 A study done in Ile Ife, Nigeria by Fadahunsi et al in 2013 showed that the commonest high-risk HPV type infection in women are 16, 53, 18 and 52. 33 Macroscopically, the tumour can be exophytic or endophytic invading surrounding structures. 10,14 The keratinizing type is composed of whorls of malignant squamous epithelial cells with individual keratinization that may be surrounding pearls of keratin.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
“…In 1983 and 1984 Dr. Harald Zur Hausen was able to isolate the HPV type 16 and 18 respectively and this led to the development of the vaccine in 2006. 2,14,15,16,25,34,35 Since the discovery of HPV 16 and 18, several other high-risk HPV types capable of causing cervical carcinoma have been discovered including types 31,33,34,35,39,45,51,52,56,58,59, 66, 68 and 70. 2,14,15,16 These viruses are capable of infecting immature squamous epithelium of the stratum germinativum (basal layer) which could be easily found in areas of squamous metaplasia in the squamocolumnar junction or following erosion of the cervix.…”
Section: Introductionmentioning
confidence: 99%